2010
DOI: 10.1177/104063871002200608
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Blood Lead and Blood and Plasma δ-Aminolevulinic Acid Concentrations as Biomarkers for Lead Poisoning in Cattle

Abstract: Abstract. Lead (Pb) concentrations in whole blood and d-aminolevulinic acid (ALA) concentrations in plasma and whole blood from 37 cattle with suspected Pb exposure were determined in order to investigate the usefulness of ALA as a biological indicator for Pb poisoning in cattle. Cows were divided into 4 groups based on blood Pb, as follows: ,30 ppb (group 1), 30-100 ppb (group 2), 100-300 ppb (group 3), and .300 ppb (group 4). The derivatization reaction for ALA was improved by a greater than 2-fold measure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Recent work evaluating delta-aminolevulinic acid (ALA) in cattle suggests plasma ALA may be a good biomarker of blood lead levels. 35 One of the main mechanisms by which lead causes toxicosis is the inhibition of aminolevulinic acid dehydratase, involved in the dimerization of ALA to form porphobilinogen in red blood cells. In humans, plasma and blood ALA activity has been a useful parameter for determination of trace exposures to lead (<0.01 µg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Recent work evaluating delta-aminolevulinic acid (ALA) in cattle suggests plasma ALA may be a good biomarker of blood lead levels. 35 One of the main mechanisms by which lead causes toxicosis is the inhibition of aminolevulinic acid dehydratase, involved in the dimerization of ALA to form porphobilinogen in red blood cells. In humans, plasma and blood ALA activity has been a useful parameter for determination of trace exposures to lead (<0.01 µg/mL).…”
Section: Methodsmentioning
confidence: 99%
“…20 Andrade et al suggested that the estimation of urinary-δ-aminolevulinic acid (U-δ-ALA) is a potential biomarker of exposure to neurotoxic metals, including Pb. 21 , 22 Ahmed et al reported significantly higher levels of U-δ-ALA in lead battery repair unit workers compared to controls. 23 …”
Section: Introductionmentioning
confidence: 99%
“…It is known that heme synthesis pathway is affected by lead and production of haemoglobin is decreased leading to anaemia [4]. Heme synthesis pathway is affected by changes in the levels of necessary enzymes required for heme synthesis [5]. One of the effects of these changes is the increased levels of delta aminolevulinic acid in urine [6].…”
Section: Introductionmentioning
confidence: 99%